Manajemen Pesantren Dalam Menghadapi Perubahan - Ahmad Saifudin (Intizam, Jurnal Manajemen Pendidikan Islam, 2017)
In the history of the development of pesantren in our country, admittedly or not, the existence of the pesantren is a unifying symbol of the nation's culture, this is as a result of the occurrence of ideological collisions between foreign cultures and local culture. precisely as one of the assets capable of reducing the renewal and modernism movements, so that the Islamic renewal movement in our country cannot develop rapidly as it did in the Middle East, especially in Turkey and Egypt. The world of pesantren always changes, but not all changes that occur outside are accepted. The future of pesantren is determined by the extent to which the pesantren formulates itself into a pesantren that is able to answer the demands of the future without losing its identity. This selection process that is accepting and rejecting follows general principles that apply. Because the principle commonly adopted by the Indonesian pesantrendi world is the concept of qaidah fiqh which reads: "al-muhafadhah 'ala al-qadim al-shalih wa al-akhdzu bi al-jadid al-ashlah", preserving good traditions while adopting things much better new things.